OPEN ABDOMEN, WHAT IS NEW IN ITS SURGICAL MANAGEMENT? - Ghassan AA Nasir (Basrah Journal of Surgery, 2009)
Open abdomen is a concept that the abdomen is left open after laparotomy especially when it was done as emergency for traumatic abdomen or reopens the abdomen when signs of increase intra-abdominal pressure (IAP) causing abdominal compartment syndrome (ACS). This open abdomen must be covered temporarily till the signs of abdominal compartment syndrome (ACS) disappears and intra-abdominal pressure (IAP) returns normal, then reclose the abdomen by one of definitive procedure. It was found that Vacuum-assisted wound closure (VAWC) is the best temporary procedure to close the abdomen to get early or late fascial closure as the best definitive closure of open abdomen. Also It was found that the classification of open abdomen is so helpful in choosing the procedure for temporary and definitive closure, this classification is new thing and dependable.